Quality Assurance of Private Islamic Universities in Jambi: Standardization, Transformation, and Sustainability - Siti Raudhatul Jannah; M. Umar; Jamaluddin (IJER (Indonesian Journal of Educational Research), 2022)
This study aims to discover and reveal the dynamics of managing private Islamic universities in Jambi in meeting standards, transforming, and surviving in the midst of competition. This research is qualitative research with an ethnographic design that takes three sites of private Islamic universities in Jambi, with key informants being the Chancellor, Vice Chancellor, Head of LPM, lecturers, educators, and students. Research data collection was carried out using observation techniques, in-depth interviews, and document studies, while data analysis used flow model analysis. The results of the study show that the three universities have the same agenda for the development of Islamic sciences, with each focus on the development of multidisciplinary integrative science, the transformation of Islamic-inspired knowledge, and innovative institutions - entrepreneurship. The quality assurance of the three universities is marked by the application of higher education national standards, institutional changes from high schools to institutes, and the strengthening of distinction. IAI Yasni strengthens the uniqueness in the field of Islamic sciences and local wisdom, IAI Nusantara carries the uniqueness of Islam Nusantara, while IAI Muhammad Azim carries excellence in the field of entrepreneurship based on Malay values. The implication of this research is that Islamic universities in Jambi need to innovate continuously to be able to survive in the midst of increasingly competitive competition. This study recommends the Ministry of Religion and the coordinator of private Islamic universities affirm PTKIS, especially in the field of quality assurance.